2021
DOI: 10.1007/s40843-021-1889-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural architectures of polymer proton exchange membranes suitable for high-temperature fuel cell applications

Abstract: High-temperature proton exchange membrane (HT-PEM) fuel cells offer more advantages than low-temperature PEM fuel cells. The ideal characteristics of HT-PEMs are high conductivities, low-humidity operation conditions, adequate mechanical properties, and competitive costs. Various molecular moieties, such as benzimidazole, benzothiazole, imide, and ether ether ketone, have been introduced to polymer chain backbones to satisfy the application requirements for HT-PEMs. The most common sulfonated polymers based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 204 publications
0
14
0
Order By: Relevance
“…Proton exchange membranes (PEMs) are one of the pivotal units in PEMFCs. [1][2][3][4] Perfluorinated membranes, such as Nafion s membranes, are the most widely available commercial PEMs. However, several drawbacks such as higher cost and lower operating temperature have limited their widespread application.…”
Section: Introductionmentioning
confidence: 99%
“…Proton exchange membranes (PEMs) are one of the pivotal units in PEMFCs. [1][2][3][4] Perfluorinated membranes, such as Nafion s membranes, are the most widely available commercial PEMs. However, several drawbacks such as higher cost and lower operating temperature have limited their widespread application.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to improve transmission efficiency and reduce energy consumption, wave-transparent materials with low D f values at high frequencies and excellent thermal resistances are in demanded. , Polyimide films (PI) have been widely used at kHz and MHz frequencies due to their excellent general properties. Nevertheless, the obviously higher D f values of PIs than other nonpolar polymers, such as polytetrafluoroethylene at high frequency, limited the applications of PI films in high frequency communications at GHz or even THz bands. , Thus, reducing the D f of PI films at high frequencies became an urgent problem to be solved, and it was generally accepted that reducing the dielectric constant (D k ) via reducing polar groups or increasing free volumes can also reduce D f at the same time. , Kuo at al. reported that decreasing the densities of polar imide rings in PI mainchains by inserting benzene rings or ether groups between imide rings can reduce the D f of PI from 0.0257 to 0.004 at 10 GHz .…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature polymer proton exchange membranes (HT-PEMs) play a core role in energy storage and conversion technologies capable of bearing high-temperature conditions, like high-temperature fuel cells and high-temperature supercapacitors. Generally, HT-PEMs need high anhydrous proton conductivity, excellent mechanical strength, as well as chemical stability at high temperatures . When designing HT-PEMs, two important factors are highly required, which include high-temperature-tolerant polymer matrices and efficient anhydrous proton-conducting moieties . At present, aromatic-containing polymers are usually employed as HT-PEM matrices, such as PBI and PEEK, due to their high glass transition temperatures. Considering that some heteroatom-based chemical bonds, for example, ether bonds, are easy to break under the long-time attack from free radicals at high temperatures, researchers also developed phenyl-based polymers whose backbones are composed of pure C–C bonds, by using superacid-catalyzed polymerization or metal-catalyzed coupling polymerization .…”
Section: Introductionmentioning
confidence: 99%
“…7 When designing HT-PEMs, two important factors are highly required, which include high-temperature-tolerant polymer matrices and efficient anhydrous proton-conducting moieties. 8 At present, aromatic-containing polymers are usually employed as HT-PEM matrices, such as PBI and PEEK, due to their high glass transition temperatures. 9−17 Considering that some heteroatom-based chemical bonds, for example, ether bonds, are easy to break under the long-time attack from free radicals at high temperatures, researchers also developed phenyl-based polymers whose backbones are composed of pure C−C bonds, by using superacid-catalyzed polymerization or metal-catalyzed coupling polymerization.…”
Section: Introductionmentioning
confidence: 99%